EVALUATING SERVICE QUALITY AND ENHANCING CUSTOMER SATISFACTION: A STUDY ON JNE COURIER SERVICE - Aziz, Eliza Viandrayani; Agustin, Rissa; Hendro, Jon; Pratiwi, Rindu Giska; Soegara, Zodi; Susilawati Sugiana, Neng Susi (LPKIA, 2025)
This study explores the service quality provided by PT Jalur Nugraha Ekakurir (JNE) and its relationship with customer satisfaction. As courier services play a pivotal role in the logistics industry, understanding how service performance shapes user perception is essential for maintaining a competitive edge. A quantitative research design was adopted, utilizing structured questionnaires distributed to 50 active users of JNE's delivery services. The survey was developed based on the SERVQUAL framework, covering five primary dimensions: reliability, responsiveness, assurance, empathy, and tangibles. Data were analyzed using SPSS through descriptive statistics, validity and reliability testing, and multiple linear regression analysis to identify the most influential service quality dimensions. Results indicate that each SERVQUAL component plays a notable role in influencing customer satisfaction, particularly reliability and responsiveness, which emerged as the most influential elements. These results highlight the importance of prompt delivery, dependable service, and responsive communication in enhancing customer satisfaction. The study concludes with practical recommendations for JNE, such as improving delivery precision, strengthening real-time tracking features, and enhancing customer service support. Furthermore, this research adds contextual insights to the limited body of literature on logistics services within the Indonesian market.